Laporan Kasus : Pubertas Dini Akibat Kanker Ovarium Tipe Embrional - Reksohusodo, Subandi (Journal of Issues in Midwifery)
Embryonic carcinoma (EC) cells were the first pluripotent cells identified. These cells were derived from malignant germ cell tumors called teratocarcinomas. Embryonal carcinoma also affects young patients but is far less common than yolk sac tumor in the ovary and, when encountered, is always a component of a mixed germ cell tumor.1 Malignant germ cell tumors are subdivided into dysgerminoma and nondygerminomatous tumors. The most common types of nondysgerminomatous tumors are yolk sac and immature teratoma. Mixed germ cell tumors with embryonal carcinoma, nongestational choriocarcinoma, and polyembryoma are less common. Embryonal carcinomas, though rare, are one of the most malignant cancers arising in the ovary.2In this case report, a 4,5-year-old girl was diagnosed with suspected embryonal ovarian carcinoma after complaints having menstruation for three months, develop pubic hair and breast. This patients later had laparotomy surgical staging and undergoing chemotherapy.Â